Мистецько-громадянська позиція українських неокласиків: між європейським Сходом і Заходом - Сірик, Людмила; Siryk, Ludmila (Східноєвропейський національний університет імені Лесі Українки, 2015)
Розглядається мистецько-громадянська позиція українських неокласиків 20-их рр. ХХ ст. На основі науково-художнього матеріалу виявлено, що вона неоднозначна і своєрідна. Схід і Захід як політичні категорії трактуються негативно (з огляду на їх антигуманний і колонізаторський характер), натомість у ролі культурних категорій – як рівноцінні частини, базовані на аксіології європейської культурної традиції. Митці демонстрували прагнення єднати європейську культуру, розбиту на Схід і Захід. Вони наголошували на позитивній ролі культури в пізнавальному, виховному, світоглядному, етичному, історичному і політичному контекстах. Серед складових позиції неокласиків виділяються такі пріоритети, як традиціоналізм, універсалізм, патріотизм, примат естетико-етичних критеріїв в оцінці літератури та мистецьких явищ. Робиться висновок, що через призму досліджуваної позиції прочитується концепція, в якій порушено актуальні й тепер проблеми (напр., етосу митця, ідентичності народу, системи цінностей українського суспільства та європейської спільноти), ідеї, зокрема, культурної спільноти європейських народів, єдності різноманітностей, боротьби за право національної культури і творчої особистості на самостійний (тобто без чужих втручань і рестрикцій) розвиток, рівноправності міжкультурних зв’язків у багатонаціональному світі. The civil-art position of the Ukrainian Neoclassics in the 20-th years of the XX century between the European East and the West is considered at the article. On the basis of the scientific – art material of neoclassics is determined, that the position isn’t single -valued and original. The East and the West as the political categories are considered negative (because of their antihuman and colonial character), but in the sphere of the cultural categories – as the equal parts, based on the European cultural tradition’s axiology. The neoclassic demonstrated the desire to unite the European culture, divided on the East and West, and they underlined also the positive role of the culture in the cognitive, educational, outlook, historical, ethical and political aspects. The component of the position add such priorities as rule of the variety in unity, the superiority of the traditional, universalism, patriotism and the superiority of the esthetic – ethic criterions in the literature and art phenomena estimation. Through the prism of their position is seen the conception, in which the group of actual problems is raisen (of the background of the creator, of the identity of the nation, of the system of values of the Ukrainian society and the european community), and also the ideas : in details of the cultural community of the European nations, the unity of the variety, the fight for the rights of the national culture and of the creative personality on the independent development (the independent of somebodies interference and restrictions), of the equality of the international cultural links in the multinational world.
The artistic and civil position of the Ukrainian neoclassics: between the European East and the West
Keywords: українські неокласики; література; культурні орієнтири; Схід; Захід; європеїзм; універсалізм; Ukrainian neoclassic; literature; cultural orientation; East; West; europeism; universalism